To write the equation of a line in slope-intercept form \( y = mx + b \), you need the slope \(m\) and the y-intercept \(b\).
Given:
- Point: \((-5, 3)\)
- Slope: \(-1\)
-
Start with the slope-intercept form: \[ y = mx + b \] Substitute the slope \(m = -1\): \[ y = -x + b \]
-
Now, use the point \((-5, 3)\) to find \(b\): Substitute \(x = -5\) and \(y = 3\): \[ 3 = -(-5) + b \] \[ 3 = 5 + b \] Solving for \(b\): \[ b = 3 - 5 \] \[ b = -2 \]
-
Now, substitute back to get the equation of the line: \[ y = -x - 2 \]
So the correct response is: \[ y = -x - 2 \]